Perbandingan Morfologi dan Sifat Fisik-Kimia Tanah Inceptisol pada Dua Lansekap Berbeda Daerah Istimewa Yogyakarta - Lulu' Ayu Faezatiy; Riesca Wulanda Citra (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
Inceptisols are widely distributed soils with significant agricultural potential; however, their characteristics are strongly influenced by landscape and parent material. Understanding these variations is essential for explaining soil-forming processes and supporting appropriate land management. This study aims to compare the morphological and physico-chemical properties of Inceptisols developed under karst and volcanic landscapes in the Special Region of Yogyakarta, Indonesia. A comparative field study was conducted on two representative pedons located in Bedoyo Kulon and Berbah. Soil profile descriptions followed standard soil survey guidelines and were supported by field and laboratory analyses of selected properties, including texture, structure, pH, carbonate content, and organic matter. The results show that Bedoyo Kulon soils are characterized by Ap–Bw1–Bw2 horizons, clay texture, dark reddish-brown color, moderately acidic pH (5–6), and the presence of carbonates in subsurface horizons. In contrast, Berbah soils exhibit Ap–A1–Bw horizons, a sandy loam texture, very dark gray to gray color, a slightly acidic pH (5–5.5), and the absence of carbonates. These differences indicate that parent material and topography play a dominant role in soil development and horizon differentiation. The findings provide insights into pedogenesis in contrasting landscapes and highlight the need for site-specific soil management strategies to improve soil fertility and sustainability.